Molecular detection of Leishmania infantum and Leishmania tropica in rodent species from endemic cutaneous leishmaniasis areas in Morocco ... : الكشف الجزيئي عن الليشمانيا الطفيلية والليشمانيا المدارية في أنواع القوارض من مناطق الليشمانيا الجلدية المتوطنة في المغرب ... - Mohamed Echchakery; Carmen Chicharro; Samia Boussaa; Javier Nieto; Eugenia Carrillo; Sergio Ortega; Javier Moreno; Ali Boumezzough (OpenAlex, 2017)
Leishmaniasis remains a major public health problem in African nations, including Morocco, where little is known about the vertebrate reservoirs involved in the causal parasites' transmission cycles. The present study investigates the role of rodent species as potential reservoirs of Leishmania spp. in central Morocco, where both L. tropica and L. infantum have been reported. Rodents were caught from 22 sites in central Morocco, by using Sherman metal traps, and identified morphologically. For each specimen, genomic DNA was extracted from different tissues using the Speed Tools DNA extraction Kit. Then, samples were PCR-analyzed, targeting the SSU rRNA gene to detect Leishmania spp. DNA, followed by amplification of the internal transcribed spacer 1 (ITS1) and its sequencing to identify the species. A total of 197 rodents belonging to ten species were captured and identified: Rattus rattus (40.61%), Mus musculus (25.38%), Apodemus sylvaticus (8.63%), Mus spretus (7.11%), Meriones shawi (5.58%), Rattus ... : لا يزال داء الليشمانيات يمثل مشكلة صحية عامة رئيسية في الدول الأفريقية، بما في ذلك المغرب، حيث لا يُعرف سوى القليل عن خزانات الفقاريات المشاركة في دورات انتقال الطفيليات المسببة. تبحث هذه الدراسة في دور أنواع القوارض كمستودعات محتملة لنبات الليشمانيا في وسط المغرب، حيث تم الإبلاغ عن كل من L. tropica و L. infantum. تم صيد القوارض من 22 موقعًا في وسط المغرب، باستخدام مصائد شيرمان المعدنية، وتم تحديدها شكليًا. لكل عينة، تم استخراج الحمض النووي الجيني من أنسجة مختلفة باستخدام مجموعة استخراج الحمض النووي لأدوات السرعة. ثم تم تحليل العينات باستخدام تفاعل البوليميراز المتسلسل (PCR)، واستهداف جين الحمض النووي الريبوزي الريبوزي الريبوزي (rRNA) للكشف عن الليشمانيا. الحمض النووي، يليه تضخيم الفاصل الداخلي المكتوب 1 (ITS1) وتسلسله لتحديد الأنواع. تم التقاط وتحديد ما مجموعه 197 قارضًا ينتمون إلى عشرة أنواع: راتوس راتوس (40.61 ٪)، وعضلة الفأر (25.38 ٪)، و Apodemus sylvaticus (8.63 ٪)، و Mus spretus (7.11 ٪)، و Meriones shawi (5.58 ٪)، و Rattus norvegicus (4.57 ٪)، و Meriones libycus (3.05 ٪)، و Mastomys erythroleucus ...